Developing highly active photocatalysts: Gold-loaded ZnO for solar phenol oxidation - Cláudia G. Silva (2014)
Gold nanoparticles were loaded on ZnO materials by a double impregnation method. Materials were characterized by spectroscopic, microscopic and N-2 adsorption techniques, and tested on the photocatalytic oxidation of phenol in aqueous solutions, under simulated solar light. Compared with bare ZnO, the Auloaded catalysts presented increased activity, which has been evaluated in terms of the pseudo-first-order kinetic constant (k(app)) and phenol mineralization. The best activities were obtained with the Au-loaded ZnO samples produced by chemical vapor deposition, and by thermal decomposition of zinc acetate (k(app) = 5.6 min(-1) mg(Au)(-1) for both materials), achieving mineralizations of 92% and 82%, respectively. Depending on the ZnO material, on the gold nanoparticle dimensions and on the irradiation wavelength used, gold particles may act as electron sinks or light harvesters. Selective trapping of photogenerated holes and radicals by selective scavengers showed that holes are crucial, but free radicals do also participate on phenol's photodegradation pathway.